Sonographic Crepitus, a Point-of-Care Ultrasound Finding - Brian Kohen; Michael Halperin; Gloria Felix; Trevor Dixon; Michelle Montenegro; Fenil Patel (CINQUILL Medical Publishers Inc., 2022)
Necrotizing fasciitis is a life-threatening polymicrobial skin and soft tissue infection that requires prompt diagnosis and treatment. Delays in diagnosis and treatment can result in an increase in morbidity and mortality [1]. Necrotizing fasciitis has historically been a clinical diagnosis. Patients with a high clinical suspicion for necrotizing fasciitis generally receive antibiotics and undergo emergent surgical debridement. In some cases, necrotizing fasciitis may be clinically difficult to differentiate from other skin and soft tissue infections such as severe cellulitis and abscesses. In such cases, POCUS may assist in diagnosis and has been shown to have a positive impact in expediting care [2,3]. Below, we describe a unique sonographic finding in a patient diagnosed with necrotizing fasciitis.